Faktor Konsistensi Sahilin dalam Kesenian Tembang Batanghari Sembilan - Feri Firmansyah; Irfan Kurniawan (SENDRATASIK UNP, 2023)
This article is the result of research which aims to describe one of the Tembang Batanghari Sembilan artists named Sahilin. The research is based on the Sahilin phenomenon which is consistent with the art of Tembang Batanghari Sembilan from early to old age. To describe Sahilin's consistency, data collection was carried out by observation, interviews and documentation. Next, the data will be presented descriptively, through the results of interpretive analysis. The research results showed that there were 4 main factors that influenced Sahilin's consistency in this art, namely; artistic talent, encouragement and upbringing from his father, social support, enjoyment because of function.